PWE-014 Is home parenteral nutrition burdensome in advanced cancer patients with malignant bowel obstruction?. (June 2019) - Patel, PS; Keane, N; Fragkos, K; O'Hanlon, F; Cauldwell, K; Rogers, J; Obbard, S; Barragry, J; Sebepos-Rogers, G; Mehta, S; Rahman, F; Di Caro, S
Abstract : Introduction: Use of home parenteral nutrition (HPN) in advanced cancer patients with malignant bowel obstruction (MBO) who have developed intestinal failure (IF), is controversial. Controversies relate to financial, cultural, and ethical issues, including the risk that HPN is burdensome for the patient and carer. We examined what burdens are placed when HPN is initiated. Methods: Retrospective cohort study of adults admitted to University College London Hospital with MBO and started on HPN between 1.1.16 and 31.12.16 with readmissions until 31.12.17. Data were analysed using mean (SD), median (range) and n (%). Survival was examined using Kaplan Meier curves. Results: 10 patients with 20 MBO admissions were started on HPN (mean±SD age: 55.3±13.9 yrs, 80% female). Primary malignancies were 50% gynaecological and 50% lower GI with metastases (70% subdiaphragmatically). Median weight and BMI on admission were normal (54.8 kg, 4–7 kg; 19.1 kg/m 2, 1–3), though, patients presented with significant weight loss (9.1%, 3.–1.1%). HPN was more likely to be set-up on the 2nd admission with BO. HPN delayed inpatient discharge by median 2 days (–) due to lack of communication within and between Oncology and Nutrition teams. Median duration of HPN was 196 days (–51). Patients were on PN 7 days/wk (–), with n=8/10 utilizing nursing input for PN (dis)connection. For those who were nursed this meant –4 visits/wk by homecare nurses for PN (dis)connection. Reasons for stopping HPN completely included: death (n=5), were end of life (n=2) or eating (i.e. BO resolved), suggesting flexibility to stop HPN to patients' circumstances. Decision to stop HPN was not contentious in any case. Post HPN discharge, median readmissions were 3, and 0 due to HPN. Follow-up appointments were mostly in oncology than nutrition clinics (5.5 vs 3 follow-ups). There was a 3m longer survival in those on HPN (median survival: 9 m for HPN patients, 4m in patients not on HPN). No HPN complications were observed over the 1 yr follow-up. Conclusion: HPN is more likely to be set up during the 2nd admission for MBO. HPN did not place a substantial burden on the patient with regards to readmissions and follow-up visits to hospital or discharge delays. Nursing visits, in addition to other service visits (e.g. GP, palliative care) could be perceived as burdensome by patients. These factors could potentially be alleviated by seamless integrated care among services. Survival was longer in HPN patients. Further research in larger settings and quality of life factors need to be weighed in decision making.